2016
DOI: 10.4315/0362-028x.jfp-15-437
|View full text |Cite
|
Sign up to set email alerts
|

Population Dynamics of Aspergillus Section Nigri Species on Vineyard Samples of Grapes and Raisins

Abstract: Several species of Aspergillus section Nigri, including potential mycotoxin producers, are common residents of grape vineyards, but the relative population size of individual species throughout the growing season is difficult to determine using traditional isolation and identification methods. Using a quantitative droplet digital PCR (ddPCR) method in combination with dilution plating, total Aspergillus section Nigri populations and relative proportions of A. niger, A. welwitschiae, A. carbonarius, and A. tubi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Applications of dPCR for agriculture are emerging, and include screening for genetically modified organisms in seed samples ( Fu et al, 2015 ), studies on populations dynamics of four species of Aspergillus infection on grapes ( Palumbo et al, 2016 ), detection of low levels of Phytophthora nicotianae in environmental samples ( Blaya et al, 2016 ) and studies of virus transmission and infection on grape vines ( Bahder et al, 2016 ). However, to our knowledge, no studies to date have used dPCR to detect fungicide resistance in field samples of crop plants.…”
Section: Introductionmentioning
confidence: 99%
“…Applications of dPCR for agriculture are emerging, and include screening for genetically modified organisms in seed samples ( Fu et al, 2015 ), studies on populations dynamics of four species of Aspergillus infection on grapes ( Palumbo et al, 2016 ), detection of low levels of Phytophthora nicotianae in environmental samples ( Blaya et al, 2016 ) and studies of virus transmission and infection on grape vines ( Bahder et al, 2016 ). However, to our knowledge, no studies to date have used dPCR to detect fungicide resistance in field samples of crop plants.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that among the Aspergillus section Nigri species described, 11 have been described and isolated from grapes, with A. carbonarius , A. tubingensis and A. niger being those with the highest occurrence and representation, and A. carbonarius the predominant species regarding OTA production and contamination of grapes . The necessity for determination of the most common black aspergilli in grapes has led to the development of numerous endpoint and real‐time PCR methods capable of detecting the species of interest.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that among the Aspergillus section Nigri species described, 11 have been described and isolated from grapes, with A. carbonarius, A. tubingensis and A. niger being those with the highest occurrence and representation, and A. carbonarius the predominant species regarding OTA production and contamination of grapes. 2,5,35 The necessity for determination of the most common black aspergilli in grapes has led to the development of numerous endpoint and real-time PCR methods capable of detecting the species of interest. These methods have proved accurate and replicable; however, although allowing the detection of certain Aspergillus species set as specific targets in each PCR assay, in the case of end-point PCR they are laborious since they require more than one step for the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen out of the twenty-seven currently recognised black aspergilli have been documented as colonisers of dried vine fruits up to date [ 5 , 32 , 33 , 34 , 35 ]. Nevertheless, only a few studies reported more than five species from one type of substrate [ 31 , 32 , 33 , 34 , 35 , 36 ]. The most dominant and, simultaneously, most genetically diverse species in our study (fourteen genotypes) was A. tubingensis .…”
Section: Discussionmentioning
confidence: 99%